Infant feeding practices and risk of preschool obesity in AlAin, UAE: A cross-sectional study. - Dana AlTarrah; Julie Lanigan; Jack Feehan; Ayesha S Al Dhaheri; Syed M Shah; Leila Cheikh Ismail; Atul Singhal (Public Library of Science (PLoS), 2024)
Early childhood obesity is serious public health problem, and poses a risk of obesity in later life. The study aimed to investigate whether infant feeding affects risk of overweight and obesity in preschool children in the United Arab Emirates (UAE). A cross-sectional study was carried out. Data was collected in a kindergarten in Al Ain, UAE. One hundred and fifty parents and preschool children aged 2 to 6 years participated in the study. Univariate and multivariate linear regression were used to investigate associations. A longer duration of breastfeeding and later introduction of complementary foods were associated with a lower BMI z-score in preschool children. Each month of any breastfeeding was associated with a lower BMI z-score in the unadjusted model (β = -0.03; 95% CI -0.05, -0.01; p = 0.01), and each month increase in the age of introducing complementary foods was associated with a lower BMI z-score in the unadjusted model (β = -0.43; 95% CI: -0.60 to-0.027; p<0.001). These associations remained after adjustment for potential confounding factors (age, sex, maternal BMI, maternal education level, mother's age, social class, father's BMI) for duration of breastfeedinig (β = -0.02; 95% CI: -0.05 to 0.00; p<0.001) and age of complementary feeding (β = -0.39; 95% CI: -0.57 to-0.21; p<0.001). Poor infant feeding practices (shorter duration of breastfeedinig and early introduction of complementary foods) were found to be associated with higher BMI in preschool children. Promoting appropriate proper infant feeding practices in line with recommendations could be one strategy to help prevent childhood obesity in the UAE.